1972
DOI: 10.2134/agronj1972.00021962006400020036x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting Asymbiotic Nitrogen Fixation in Soils as Measured by 15N Enrichment1

Abstract: The use of the isotopic 15N technique to measure asymbiotic N fixation in soils has been reported by very few workers, despite the obvious advantages of the technique in assessing the importance of this fixation in agricultural soils. The effect of glucose plus cellulose (0 and 0.5% glucose + 0.5% cellulose), glucose alone (0, 0.04, 0.2, 1.0 and 5.0% on dry soil weight basis), incubation temperature, method of soil aeration, and atmospheric composition on N fixation in soil in a closed system using 15N was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…It has been suggested that nitrogen fixation by free-living bacteria in cultivated land is widespread but generally at low rates (175). Measurements of acetylene reduction or incorporation of "'N2 into carbohydrateor cellulose-amended soils have demonstrated potentials for nitrogen fixation, which could occur periodically in nature and account for appreciable gains in nitrogen (18,37,49,69,75,93,122,124,151,165,185).…”
Section: Current Concepts Of Nitrogenmentioning
confidence: 99%
“…It has been suggested that nitrogen fixation by free-living bacteria in cultivated land is widespread but generally at low rates (175). Measurements of acetylene reduction or incorporation of "'N2 into carbohydrateor cellulose-amended soils have demonstrated potentials for nitrogen fixation, which could occur periodically in nature and account for appreciable gains in nitrogen (18,37,49,69,75,93,122,124,151,165,185).…”
Section: Current Concepts Of Nitrogenmentioning
confidence: 99%